Some properties of natural rubber from latex-timber clones - Eng A H; Kawahara S; Masahuling B; Muniandy V; Othman H; Ramli O (Journal of Rubber Research, 2001)
Several properties of natural rubber from latex-timber clones, which produce high timber and latex yields, were examined. Of the 28 clones, 14 clones were found to produce high dry rubber content (DRC) latices, i.e. above 41;, most of which were from the RRIM 2000 series. No latices were found to have a DRC below 34;. Except for Mooney viscosity, all the clonal rubbers could satisfy the specifications of SMR-CV scheme. The mooney viscosity of 15 clonal rubbers was observed to exceed the limit specified in the SMR-CV 60 scheme. However, the viscosity of such rubbers can be reduced by blending the latices with other latices having low viscosity rubbers before processing them into dry rubberrs. The molecular weight distributions of the clonal rubbers were either unimodal with a peak in high molecular weight region, or bimodal with a small peak in the low molecular weight region. On account of this, the polydispersity, 3.1~5.4, was narrower than the range of 2.5~10 reported previously. The number average and weight average molecular weights of the rubber were found to be in the range of 2.77X10 5~7.06X10 5 and 1.50X10 6~2.34X10 6, respectively. The correlations between Mooney viscosity and Wallace plasticity, Mooney viscosity and molecular weight were also found.
Keywords: Dry rubber content(DRC); Latex yields; Latex-timber clones; Molecular weight; Mooney viscosity; Properties; SMR-CV; Wallace plasticity